Spirulina platensis ameliorates arsenic-mediated uterine damage and ovarian steroidogenic disorder - Shamima Khatun; Moulima Maity; Hasina Perveen; Moumita Dash; Sandip Chattopadhyay (Canadian Science Publishing, 2018)
Novel, non-invasive, painless oral therapeutic agents are needed to replace the painful conventional treatment of arsenic-associated health hazards with metal chelators. Our aim was to examine the effect of spirulina (Spirulina platensis (Geitler, 1925)) on arsenic-mediated uterine toxicity. Female Wistar rats were divided equally into four experimental treatment groups: control group, sodium arsenite group (1.0 mg/100 g body mass), spirulina placebo group (20 mg/100 g body mass), and sodium arsenite + spirulina group. In contrast with the control group, spectrophotometric and electrozymographic evaluation revealed that rats that ingested arsenic for 8 d showed significant diminution of the activities of superoxide dismutase, catalase, and peroxidase (p < 0.001). Mutagenic uterine DNA breakage and tissue damage were prominent following arsenic consumption by the rats. Oral delivery of spirulina resulted in a significant amelioration of arsenic-induced adverse oxidative stress and genotoxic state of rats. A significant low-signaling (p < 0.001) of gonadotropins and estradiol was also noted in the arsenic-treated rats, which was terminated by spirulina; this arsenic-primed adverse effect was significant (p < 0.05, p < 0.01). The spirulina treatment mechanism could be associated with augmentation of the antioxidant defense system that protects the arsenic-mediated pathological state of the uterus.